Non-specific impairment of Lung Function on Spirometery in Patients with Chronic Hepatitis-C - Zuberi, Faisal Faiyaz (Pak J Med Sci, 2019)
OBJECTIVES: To document frequency of non-specific impairment of lung functions (NILF) in patients of HCV and to compare according to gender, genotype, liver fibrosis score and smoking status. METHODS: Patients of chronic hepatitis C were included after informed consent. Demographic data was recorded, and they underwent baseline investigations, fibroscan, abdominal ultrasound and PFT. Patients were segregated on basis of gender, fibroscan stages and smoking status. NILF was labelled if any two of three criteria are fulfilled (a) FVC < 80% of Predicted, (b) FEV1 < 80% Predicted, (c) FEV1/FVC ≥ 70. RESULTS: Two hundred thirty four patients were of chronic HCV who fulfilled the selection criteria were inducted in study. These included 49.6% males and 50.4% females. There were 15.0% smokers, 16.2% were ex-smokers while 68.8% were never smokers. NILF was present in 130 (55.6%) out of which 61.5% were female and 38.5% were male (p <0.001), its presence in smokers was 56.2% and in never smokers was 55.3% (p=0.507). Presence of NILF increased with Fibroscan stages from F1 to F4 (p <0.001). CONCLUSIONS: NILF pattern on spirometry with normal chest radiograph is common among HCV patients. It was found more common in females and frequency increased progressively with fibro scan stages.